9C.02: EFFECT OF DIFFERENT ANTIHYPERTENSIVE DRUG CLASSES ON SURVIVAL IN UNILATERAL AND BILATERAL RENAL ARTERY STENOSIS. (June 2015) - Barker, E.; Desmukh, H.; Levin, D.; George, J.
Abstract : Objective: Randomized trials in atherosclerotic renovascular disease (ARVD) have failed to show a survival advantage of renovascular stenting relative to medical management. The comparative survival benefit of widely used antihypertensive drug classes has not been previously studied in this cohort. We aimed to determine this among individuals with unilateral (URAS) and bilateral renal artery stenosis (BRAS). Design and method: In this retrospective record-linkage study, anonymised data over a 6 year period on approximately 800, 000 people across Tayside and Fife, Scotland, was studied. Magnetic resonance and percutaneous angiography reports were used to select controls and subjects with URAS and BRAS. Biochemistry, prescribing and demographic data were accessed via electronic patient records and laboratory reports. ICD10 codes were used to identify cardiovascular events. Survival in each group was determined using Cox proportional hazard analysis and Kaplan-Meier survival curves, adjusted for all relevant covariates. A time-updated analysis was performed to confirm the findings. Results: The mean follow-up duration was 3.5 years. Mortality rates were 36.0% and 50.8% in URAS and BRAS respectively. Baseline eGFR (URAS (P = 4.07x10-8, HR = 0.966(0.95, 0.97), BRAS (P = 0.001, HR = 0.966(0.94, 0.99)), duration of diabetes (URAS (P = 0.02, HR = 1.04(1, 1.07), BRAS (P = 0.001, HR = 1.08(1.03, 1.13)) and age (URAS (P = 0.001, HR = 1.04(1.01, 1.06), BRAS (P = 0.01, HR = 1.05(1.01, 1.09)) independently predicted survival. 22% of URAS and 42% of BRAS patients underwent revascularization, however stent in-situ at baseline did not significantly improve survival in URAS (P = 0.8) or BRAS (P = 0.8). Baseline use of calcium channel blockers (CCBs) (P = 0.01, HR = 0.67(0.46, 1.00)) and angiotensin converting enzyme inhibitors (ACEIs) (P = 0.008, HR = 0.35(0.16, 0.76)) were independently associated with survival in URAS. In the time-updated analysis, ACEI use did not improve survival in URAS (P = 0.443) or BRAS (P = 0.06). However, use of CCBs was associated with a survival advantage for both populations; URAS P = 1.88x10–5, HR = 0.44(0.30, 0.64), BRAS P = 0.001, HR = 0.38, (0.21, 0.67). Conclusions: This study is consistent with published data showing no additional benefit of revascularization. CCBs significantly increase survival in both URAS and BRAS. Further prospective studies should identify whether this occurs independently of a reduction in blood pressure.